Rotational Atherectomy or Balloon-Based Techniques to Prepare Severely Calcified Coronary Lesions - Rheude, Tobias; Fitzgerald, Sean; Allali, Abdelhakim; Mashayekhi, Kambis; Gori, Tommaso; Cuculi, Florim; Kufner, Sebastian; Hemetsberger, Rayyan; Sulimov, Dmitriy S; Rai, Himanshu; Ayoub, Mohamed; Bossard, Matthias; et al. (JACC. Cardiovascular interventions, 2022)
The comparative efficacy of percutaneous techniques for the preparation of calcified lesions before stenting remains poorly studied.BACKGROUNDThe comparative efficacy of percutaneous techniques for the preparation of calcified lesions before stenting remains poorly studied.This study sought to compare the performance of up-front rotational atherectomy (RA) or balloon-based techniques before drug-eluting stent implantation in severely calcified coronary lesions as assessed by angiography and optical coherence tomography (OCT).OBJECTIVESThis study sought to compare the performance of up-front rotational atherectomy (RA) or balloon-based techniques before drug-eluting stent implantation in severely calcified coronary lesions as assessed by angiography and optical coherence tomography (OCT).Patient-level data from the PREPARE-CALC (Comparison of Strategies to Prepare Severely Calcified Coronary Lesions) and ISAR-CALC (Comparison of Strategies to Prepare Severely Calcified Coronary Lesions) randomized trials were pooled. The primary endpoint was stent expansion as assessed by OCT imaging. The secondary endpoints included stent eccentricity, stent asymmetry, angiographic acute lumen gain, strategy success and in-hospital occurrence of cardiac death, target vessel myocardial infarction, and repeat revascularization.METHODSPatient-level data from the PREPARE-CALC (Comparison of Strategies to Prepare Severely Calcified Coronary Lesions) and ISAR-CALC (Comparison of Strategies to Prepare Severely Calcified Coronary Lesions) randomized trials were pooled. The primary endpoint was stent expansion as assessed by OCT imaging. The secondary endpoints included stent eccentricity, stent asymmetry, angiographic acute lumen gain, strategy success and in-hospital occurrence of cardiac death, target vessel myocardial infarction, and repeat revascularization.Among 274 patients originally randomized, 200 participants with available OCT data after lesion preparation with RA (n = 63), a modified balloon (MB, n = 103), or a super high-pressure balloon (n = 34) before stenting were analyzed. The use of RA versus MB or a super high-pressure balloon led to comparable stent expansion (73.2% ± 11.6% vs 70.8% ± 13.6% vs 71.8% ± 12.2%, P = 0.49) and stent asymmetry (P = 0.83). Compared with RA or MB, a super high-pressure balloon was associated with less stent eccentricity (P = 0.03) with a numerically higher acute lumen gain, albeit not significantly different (P = 0.08). Strategy success was more frequent with RA versus MB (P = 0.002) and numerically more frequent with RA versus a super high-pressure balloon (P = 0.06). Clinical outcomes did not differ between groups.RESULTSAmong 274 patients originally randomized, 200 participants with available OCT data after lesion preparation with RA (n = 63), a modified balloon (MB, n = 103), or a super high-pressure balloon (n = 34) before stenting were analyzed. The use of RA versus MB or a super high-pressure balloon led to comparable stent expansion (73.2% ± 11.6% vs 70.8% ± 13.6% vs 71.8% ± 12.2%, P = 0.49) and stent asymmetry (P = 0.83). Compared with RA or MB, a super high-pressure balloon was associated with less stent eccentricity (P = 0.03) with a numerically higher acute lumen gain, albeit not significantly different (P = 0.08). Strategy success was more frequent with RA versus MB (P = 0.002) and numerically more frequent with RA versus a super high-pressure balloon (P = 0.06). Clinical outcomes did not differ between groups.In patients with severely calcified lesions undergoing drug-eluting stent implantation, lesion preparation with RA, MB, or a super high-pressure balloon was associated with comparable stent expansion. A super high-pressure balloon is associated with less stent eccentricity, whereas strategy success is more frequent with RA.CONCLUSIONSIn patients with severely calcified lesions undergoing drug-eluting stent implantation, lesion preparation with RA, MB, or a super high-pressure balloon was associated with comparable stent expansion. A super high-pressure balloon is associated with less stent eccentricity, whereas strategy success is more frequent with RA.